Risk factors, management and prevention of transfusion-related acute lung injury: a comprehensive update - Kuldanek, Susan A. (Expert Rev Hematol, 2019)
INTRODUCTION: Despite mitigation strategies that include the exclusion of females from plasma donation or the exclusion of females with a history of pregnancy or known anti-leukocyte antibody, transfusion-related acute lung injury (TRALI) remains a leading cause of transfusion-related morbidity and mortality. AREAS COVERED: The definition of TRALI is discussed and re-aligned with the new Berlin Diagnostic Criteria for the acute respiratory distress syndrome (ARDS). The risk factors associated with TRALI are summarized as are the mitigation strategies to further reduce TRALI. The emerging basic research studies that may translate to clinical therapeutics for the prevention or treatment of TRALI are discussed. EXPERT OPINION: At risk patients, including the genetic factors that may predispose patients to TRALI are summarized and discussed. The re-definition of TRALI employing the Berlin Criteria for ARDS will allow for increased recognition and improved research into pathophysiology and mitigation to reduce this fatal complication of hemotherapy.